Gold nanoparticles saturable absorber for ultrashort pulse generation in fibre lasers - Naharuddin, Noor Zirwatul Ahlam (2021)
The advantages of ultrashort pulse lasers have triggered a technological tsunami in the laser field, putting pressure on researchers to discover the simplest fabrication method and thus effectively improve the saturable absorber (SA) preparation technique. The optical property of saturable absorption is directly associated to the embedded materials in SAs themselves. Thus, manipulation of the embedded materials may improve the overall performance of the SA. Metallic nanostructures have been known for their optical properties due to the effect of surface plasmon resonance. Among the metallic nanostructures, gold nanoparticles (Au-NPs) are widely investigated due to its saturable and reverse saturable absorption properties. These properties can be tailored to cater for various applications by manipulating its size and shape. There are three important aspects in this research work which include the synthesis of Au-NPs in tetrahydrofuran by pulsed laser ablation, validation of the ablated Au-NPs as a SA in generating mode-locked pulses and investigation on the effect of Au-NP size towards optical pulse profiles. The proposed synthesis of Au-NPs in tetrahydrofuran with stirring condition produced a good size distribution of spherical Au-NPs ranging from 6.0 to 11.5 nm. The size reduction was influenced by the ablation time increment from 7 to 30 minutes. The effect of stirring was also confirmed by comparing the ablated material size without stirring. However, the biggest challenge of using this method was the low yield of ablated Au-NPs. In order to study the effect of Au- NP size, commercially available Au-NPs of varied sizes were purchased; 10, 20, 40 60 and 80 nm. These two batches would be prepared as fillers inside polydimethylsiloxane (PDMS) polymer matrix. To fabricate a mode-locker that can support evanescent wave propagation, a tapered fibre was selected as the preferred waveguide. The embodiment of Au-NPs with PDMS on the tapered fibre was deposited using a spin coating technique. The longitudinal encapsulation of Au-NP/PDMS enables interaction between evanescent wave and matter (surrounding medium). The fabricated Au-NP-based SA was characterized using a twin balance photo-detection method to obtain its saturation fluence, non-saturable loss and modulation depth. The functionality of the fabricated Au-NP-based SA was proven by incorporating it in a ring cavity erbium-doped fibre laser as a result of optical pulse generation. The same laser cavity was used throughout the research work to minimize uncertainties of loss and dispersion. Based on the experimental findings, both batches of Au-NPs were proven to be able to generate ultrashort pulse with a pulse duration of less than 1 picosecond. This marks the most significant finding of the research work. For the ablated Au-NPs, the average size of 7.8 nm was successfully tested to generate mode-locked pulse at 1554.5 nm with duration in the range of 916 – 994 fs. Even though that the modulation depth of the fabricated SA was only 0.4%, a stable pulse was produced. For the commercially available Au-NPs, mode-locked pulse was attained for all sizes to verify the finding from the previous experiment (ablated Au-NPs). The lasing performance was evaluated by comparing SA characteristics and pulse qualities among the sizes. The optimum pulse performance was realized when the SA was fabricated with 20 and 40 nm Au-NP size. For the former, the timebandwidth product of 0.34 was demonstrated which was the closest to its bandwidth-limited pulse. For the former, the fabricated SA exhibited 4.0% modulation depth and average pulse duration of 886.7 fs. From the experimental findings, larger Au-NP size of 60 and 80 nm had the tendency to scatter more lights due to its larger cross section. Therefore, the highest transmission loss of 8.56 dB was obtained for 80 nm Au-NP size and the pulse quality deteriorated to 1062.3 fs. The research work has demonstrated the functionality of Au-NPs as a saturable absorption material to generate ultrashort pulses. In addition, the size of nanomaterials has influenced on the characteristics of saturable absorbers that shapes the quality of laser pulse.